The "sacred" standing for the "fallen" spirits: Yasukuni Shrine and memory of war. Issue 4 (1st October 2016) - Lee, JongHwa
ABSTRACT: This essay examines the rhetoric/politics of Yasukuni Shrine as an experiential memory-scape, a material and discursive ground to frame and enact banal patriotism and militant nationalism. As a powerful mnemonic and rhetorical institution, Yasukuni Shrine (re)produces a nationalistic narrative and identity by (con)fusing natural feelings of individual grief and cultural tradition of commemoration with national heritage of banal patriotism. By (con)fusing what is "particular" and "universal, " Yasukuni Shrine establishes its rhetorical ground to justify a "banal" sense of patriotism that slips into the "ordinary yet honorable" fervor of militant nationalism, while effectively evading its moral/ethical reflexivity.